Systemic Chemotherapy for Progression of Brain Metastases in Extensive-Stage Small Cell Lung Cancer - Nagla Abdel Karim; Ananta Bhatt; Lauren Chiec; Richard Curry (Case Reports in Oncological Medicine)
Lung cancer is the most common cause of cancer related mortality in men and women. Approximately 15% of lung cancers are small cell type. Chemotherapy and radiation are the mainstay treatments. Currently, the standard chemotherapy regimen includes platinum/etoposide. For extensive small cell lung cancer, irinotecan and cisplatin have also been used. Patients with relapsed small cell lung cancer have a very poor prognosis, and the morbidity increases with brain metastases. Approximately 10%–14% of small cell lung cancer patients exhibit brain metastases at the time of diagnosis, which increases to 50%–80% as the disease progresses. Mean survival with brain metastases is reported to be less than six months, thus calling for improved regimens. Here we present a case series of patients treated with irinotecan for progressive brain metastases in small cell lung cancer, which serves as a reminder of the role of systemic chemotherapy in this setting.